Comportamento mecânico em fadiga da liga de titânio beta metaestável Ti-5553 - Campanelli, Leonardo Contri (2016)
The microstructure of metastable beta Ti alloys is a decisive factor that governs their properties and, therefore, the assessment of the relation between the microstructure and the fatigue response means an advance in the still incipient knowledge on these alloys. The purpose of this work was to study the fatigue behavior of Ti-5Al-5Mo-5V-3Cr (Ti-5553) alloy recently developed for landing gear applications, which was kindly supplied by Boeing for this work. The material was subjected to different heat treatments (BASCA and double aging) aiming at to comprehend the influence of the alpha phase precipitation over the beta matrix, as well as to understand the effect of hydrogen even in commercially acceptable contents. BASCA microstructure comprised large laths and fine needles of primary and secondary alpha phase respectively, with a film of approximately 2 μm of thickness at grain boundaries. A refined and aligned structure of alpha phase resulted from the double aging treatment, reducing to 0.2 μm the thickness of the grain boundary alpha film. The fatigue limit at 5x106 cycles raised by the standardized staircase method initially showed an improved result for the harder microstructure, which resulted from the double aging, for 100 ppm of hydrogen. The fatigue crack nucleation, whether at the surface or subsurface, was attributed to the thickness of the grain boundary alpha film. In spite of this film brittleness, crack propagation predominantly occurred through the grains and exhibited quasi-cleavage facets and dimples. For the structure arising from the BASCA treatment, the decrease of the hydrogen content for 25 ppm led to a significant increase of the fatigue resistance as a consequence of the absence of hydrides and the higher toughness, overcoming the effect of the coarse alpha phase particles in the beta phase matrix.